Respuestas
Respuesta dada por:
2
Hola,
![(a - b)(a + b) (a - b)(a + b)](https://tex.z-dn.net/?f=%28a+-+b%29%28a+%2B+b%29)
Diferencia de Cuadrados:
![(a - b)(a + b) \\ = {a}^{2} - ab + ab - {b}^{2} \\ = {a}^{2} - {b}^{2} (a - b)(a + b) \\ = {a}^{2} - ab + ab - {b}^{2} \\ = {a}^{2} - {b}^{2}](https://tex.z-dn.net/?f=%28a+-+b%29%28a+%2B+b%29+%5C%5C++%3D++%7Ba%7D%5E%7B2%7D+-+ab+%2B+ab+-++%7Bb%7D%5E%7B2%7D+++%5C%5C+%3D++%7Ba%7D%5E%7B2%7D++-++%7Bb%7D%5E%7B2%7D+)
Respuesta:
![(a - b)(a + b)= {a}^{2} - {b}^{2} (a - b)(a + b)= {a}^{2} - {b}^{2}](https://tex.z-dn.net/?f=%28a+-+b%29%28a+%2B+b%29%3D++%7Ba%7D%5E%7B2%7D++-++%7Bb%7D%5E%7B2%7D+)
Espero que te sirva, Saludos.
Diferencia de Cuadrados:
Respuesta:
Espero que te sirva, Saludos.
Preguntas similares
hace 6 años
hace 6 años
hace 6 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años